239 IS ORTHOSTATIC HYPOTENSION ASSOCIATED WITH ALTERED CEREBRAL PERFUSION DURING ACTIVE STANDING?. (18th November 2021) - Claffey, P; Pérez-Denia, L; Dyer, A; McNicholas, T; Briggs, R; Finucane, C; Kenny, R A
Abstract: Background: Orthostatic Hypotension (OH) is associated with poor health outcomes in later life including depression, cognitive impairment, frailty and falls. Whilst it is hypothesised that OH compromises cerebral autoregulation leading to hypoperfusion, this has not been robustly demonstrated to date. This study investigated the association between OH and cerebral perfusion during orthostasis using a non-invasive surrogate of cerebral perfusion, Near Infrared Spectroscopy (NIRS). Methods: Four hundred and ninety one participants (58% female, median age 65, IQR 38–92) attending a falls and syncope service underwent measurement of beat-to-beat blood pressure (BP) by finometry and real-time frontal lobe perfusion (% TSI: Tissue Saturation Index) by NIRS during the active stand manoeuvre. We examined the association between OH and change in cerebral perfusion (delta TSI) using mixed-effects linear regression, with adjustment for important clinical covariates. Results: Nearly two-fifths of the sample (189/491, 38.5%) met criteria for OH occurring between 30 and 120 seconds after standing. Using mixed effects linear regression models, we observed a significant relationship between OH and TSI at the same timepoint (β −0.53, −0.59 to −0.46, p < 0.001) which persisted following adjustment for confounders including age, sex, baseline blood pressure, cerebrovascular and cardiovascular disease, depression/anxiety, diabetes, systolic blood pressure, antihypertensives, and antidepressants (β −0.51, −0.58 to −0.44, p < 0.001). Cerebral perfusion levels differed for those with OH compared to those without. Conclusion: OH is independently associated with lower frontal lobe cerebral perfusion. This association may indicate disruption to dynamic cerebral autoregulation and explain the significant link between OH and poor health outcomes.